Barriers to school attendance and gender inequality: Empirical evidence from a sample of Ghanaian schoolchildren. (June 2016) - Wolf, Sharon; McCoy, Dana C; Godfrey, Erin B
Governments in sub-Saharan Africa have made marked efforts to increase school enrollment. Yet attendance and completion rates remain low, particularly for girls. This study examines the reasons that school children do not attend school in a sample of Ghanaian students. Girls were more likely to miss school because a family member was sick, whereas boys were more likely to miss school due to work. Caregivers' inability to pay school fees and belief that it is better to educate boys than girls were related to lower school attendance for girls but not for boys. Implications of the findings to inform efforts to improve educational access for all children are discussed.